When recall gets stressful: comparing Papuan Malay and German listeners' lexical storage of word stress - Constantijn Kaland (Laboratory Phonology)
Recent studies indicated that Papuan Malay, spoken in the Eastern provinces of Indonesia, has regular penultimate word stress. Only when schwa occurs in the penultimate syllable, stress is ultimate, making the pattern highly predictable. Acoustic, lexical and perception studies showed that these stress patterns offer disambiguating cues that Papuan Malay listeners can use in word recognition. It is however poorly understood to what extent these predictable patterns are stored lexically in this language, and in fixed stress languages in general. The current study investigates this question by means of stress recall tasks comparing Papuan Malay with German, the latter being analyzed as a free (lexical) stress language. To this end, a critical review of the previous literature is given regarding the methodological comparability of stress recall tasks across languages. The tasks used in the current study replicate the stimuli and procedures used in three previous studies. Results show that Papuan Malay listeners have worse stress recall performance than German listeners, suggesting that Papuan Malay stress is not stored lexically. The outcomes are discussed with respect to the diagnosis of word stress in Papuan Malay and its typological context.